Association between Primary Care Assessment Tool (PCAT) and Assessment of Chronic Illness Care (ACIC): a Brazilian cross-sectional study - Gomes, Brenda Lorrana de Almeida; Mota, Renan Felipe Neves; Braga, Renata Sant'ana; Nunes, Cynthia Assis de Barros; Guimarães, Rafael Alves; Rodrigues, Ana Paula dos Santos; Batista, Sandro Rogério Rodrigues; Pagotto, Valéria (Frontiers in Medicine, 2024)
Aim: to analyze the association between Primary Health Care (PHC) performance and institutional ability to provide care for individuals with noncommunicable diseases (NCDs).Methods: Cross-sectional study conducted with primary care nurses and physicians in Brazil.The performance of PHC was assessed by using the Primary Care Assessment (PCAT), whereas institutional ability for the care of people with NCDs was assessed through the Assessment of Chronic Illness Care (ACIC). Pearson correlation and multiple linear regression models were used to analyze the association between the PHC attributes measured in the PCAT (independent variables) and the ACIC dimensions (dependent variables).Results: In total, 308 health professionals -190 nurses (61.7%) and 118 physicians (38.3%)at mean age 37.5 years and mean time of 6.5 years working in PHC participated of the study.On a scale of 0 to 10, the overall PCAT score was 6.74, while the ACIC score was 5.20. The PCAT score was High in only 58.8% of respondents (score >6.6). The ACIC scores showed basic institutional ability to care for people with NCDs. All ACIC dimensions have shown positive correlation to PCAT attributes, except for accessibility, continuity of care and care coordination. Conclusion: A positive association was found between PHC performance and institutional ability to care for people with NCDs. Results have evidenced the need of investing in PCH by providing technical, political, logistical and financial support to PHC units to improve PHC organization points and care for people with NCDs.